The debt crisis: a re-appraisal - Cinquetti, Carlos Alberto [UNESP] (Editora 34, 2005)
The 1980s' debt crisis is a landmark in developing economies' growth and stabilization. According to the most quoted empirical articles, external shocks and vicissitudes gave rise to crisis just because of delays in stabilization policies, engendered by internal conflicts and institutional immaturity. I review some of these papers, and find out some problems - in the measurement of shocks and foreign indebtedness, namely - whose corrections lead to opposite results: external shocks and foreign indebtedness explain that crisis regardless of domestic policies. At the same time, the strong correlation of income distribution to terms of trade changes and foreign indebtedness suggest that inequality may have contributed differently to that crisis: either through an economic channel, or through a political channel based on delays in reforms.
Keywords: External Shocks; Indebtedness; Debt Crisis; Stabilization Policies; Trade Protection; Political Economy